2011
DOI: 10.1097/fpc.0b013e32834bec2b
|View full text |Cite
|
Sign up to set email alerts
|

Acetylator status and N-acetyltransferase 2 gene polymorphisms; phenotype–genotype correlation with the sulfamethazine test

Abstract: N-acetyltransferase 2 (NAT2) catalyzes the bioactivation and/or detoxification of drugs and carcinogens. The aim of this study was to establish the correlation between the NAT2 genotype and the acetylating phenotype in a Mexican population using sulfamethazine as a probe. From a total of 122 individuals, 73 (59.8%) were slow and 49 (40.2%) were fast acetylators. Eleven individuals (9%) had the wild-type genotype (NAT2*4/NAT2*4). The most frequent genotype was NAT2*4/NAT2*5B observed in 20.66% of individuals. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The presence of slow acetylation activity SNPs has been linked to the risk of developing type 2 diabetes [7, 8]. The sample of healthy volunteers participating on this study showed a high prevalence of a slow acetylation phenotype consistent with previous reports with larger samples of Mexican [34, 37] and Central American populations [43]. This can be attributed to the admixture effect present on American mestizo groups [44, 45].…”
Section: Discussionsupporting
confidence: 86%
“…The presence of slow acetylation activity SNPs has been linked to the risk of developing type 2 diabetes [7, 8]. The sample of healthy volunteers participating on this study showed a high prevalence of a slow acetylation phenotype consistent with previous reports with larger samples of Mexican [34, 37] and Central American populations [43]. This can be attributed to the admixture effect present on American mestizo groups [44, 45].…”
Section: Discussionsupporting
confidence: 86%
“…As is apparent in Fig. , the coefficient of variation of the reported NAT2 activity is smaller in the fast than in the slow acetylator group due to a higher number of outliers, reducing the correlation between the genotype deduced phenotype and the actual enzyme activity in this group (based on previously reported data) . At least in this case, selection of genotypes with reduced activity profiles as proposed by González‐Vacarezza et al .…”
Section: Discussionmentioning
confidence: 79%
“…A 4‐SNP genotyping method has been proposed including the SNPs rs1801280, rs1799930, rs1799931 and rs1801279. However, due to the fact that in the Mexican population, the minor allele frequency of rs1801279 is below 0·05, volunteers were not tested for this allele . Accuracy of classification is expected to only increase marginally for the slow and fast acetylator genotypes by expanding from the 3‐SNP scheme to the 7‐SNP scheme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAT2 *12A, NAT2 *12C, NAT2 *13 and NAT2 *18 have also been classified as rapid alleles. The remaining alleles are considered to be slow alleles (911). …”
Section: Introductionmentioning
confidence: 99%